Investigation of acetyl migrations in furanosides - Chevallier, O. P.; Migaud, M. E. (Beilstein Journal of Organic Chemistry, 2006)
Standard reaction conditions for the desilylation of acetylated furanoside (riboside, arabinoside and xyloside) derivatives facilitate acyl migration. Conditions which favour intramolecular and intermolecular mechanisms have been identified with intermolecular transesterifications taking place under mild basic conditions when intramolecular orthoester formations are disfavoured. In acetyl ribosides, acyl migration could be prevented when desilylation was catalysed by cerium ammonium nitrate.